Halal tourism potential in North Maluku: Synergy between culture, religion, and economy - Kanaha, Ibnu; Kurniawan, Satunggale (Universitas Islam Indonesia, 2025)
IntroductionNorth Maluku, a culturally rich province with deep Islamic roots, possesses significant potential for developing halal tourism. Despite its historical Islamic sites and vibrant religious traditions, this potential remains underutilized due to infrastructural limitations and fragmented policy support.ObjectivesThis study aims to analyze the development of halal tourism in North Maluku by examining the synergy between culture, religion, and economy. It further explores the roles of local stakeholders, assesses the empowerment of micro, small, and medium enterprises, and evaluates how global halal tourism trends influence strategic regional planning.MethodUsing a descriptive qualitative approach, the research involved in-depth interviews, participatory observation, and documentation across selected sites in North Maluku. Participants included religious leaders, government officials, tourism business actors, MSMEs, and local communities engaged in Islamic cultural practices.ResultsFindings reveal that the integration of local Islamic traditions into tourism offerings enhances destination authenticity and appeal. Government interventions remain partial but show commitment through the establishment of sharia-compliant facilities. Halal tourism has empowered MSMEs, yet challenges persist in aligning community-based models with halal standards due to knowledge gaps, resource constraints, and regulatory inconsistency. Global trends in Muslim travel offer strategic opportunities for North Maluku to position itself competitively within the halal tourism market.ImplicationsThis study contributes to the theoretical understanding of halal tourism as a culturally embedded, community-driven development model. Practically, it underscores the need for regulatory clarity, investment in training, and strategic marketing. For policymakers, it offers evidence-based recommendations for developing inclusive, sustainable, and globally oriented halal tourism strategies in underdeveloped regions.Originality/NoveltyUnlike previous studies that generalize halal tourism within urban or international contexts, this research offers a region-specific perspective that highlights the importance of cultural-religious synergy. It introduces a multidimensional framework where halal tourism functions as a tool for local empowerment, identity preservation, and regional economic development.